Health Education Demonstration Method On Mothers' Knowledge About First Aid For Choking In Early Childhood - Kunbaran, Ariya; Yanti, Nova; Roza, Defia; Suryarinilsih, Yosi; Ramadini, Indri (Poltekkes Kemenkes Semarang, 2024)
Background: a total of 65 patients were diagnosed with foreign body aspiration at M. Djamil Padang Hospital during the 2017-2018 period. The age groups most frequently affected were 0-4 years (100%) in the larynx, 5-11 years (50%) in the trachea, and 0-4 years (50%) in the bronchi. Choking is a prevalent issue that can result in fatalities in some instances, necessitating a heightened level of attention. A dearth of information among parents, particularly mothers, results in a lack of awareness regarding the prevention and management of choking.Purpose: to analyze the effect of a health education demonstration method on the level of knowledge of mothers about first aid for choking in early childhood at Cahaya Ummi 2 KindergartenMethods: this study used Quasi-Experiment with the design of one group pre-post with a sample size of 43 respondents, selected through purposive sampling. The data were collected using a questionnaire and Bivariate analysis using the Wilcoxon test.Results: the findings of this study indicate that the mean knowledge score of respondents increased from 14.09 to 17.06. There is an effect health education demonstration method with the knowledge of mothers about first aid for choking in early childhood, with a p-value of 0.000.Conclusion: it is hoped that mothers will be able to apply first aid for choking quickly and appropriately in the event of an emergency.